Diplomacy and Recruitment of Mercenaries before the Battle of Žalgiris - Sven Ekdahl (Lietuvos Istorijos Studijos)
During the months preceding the battle of Žalgiris (Tannenberg/Grunwald) the diplomatic activity of the countries involved was intense. After the successful campaign of the Teutonic Order against Poland in 1409 an armistice was concluded on 8 October between Grand Master Ulrich von Jungingen and King Jagiello (Jogaila) of Poland and the war was postponed until the end of St John's Day in 1410. The truce did not include Grand Duke Vytautas and the Grand Duchy of Lithuania. An arbitration had to be announced by King Venceslas of Bohemia on 9 February 1410 at the latest.